Assessment of Maritime Piracy in East Africa : Application of Rational Choice - Routine Activities Theory and Dynamic Operational Design Planning and Assessment Approach /: Application of Rational Choice - Routine Activities Theory and Dynamic Operational Design Planning and Assessment Approach. (2017) - Vincent C. Figliomeni
No abstract available